2004
DOI: 10.1038/sj.onc.1207913
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Sp1 positively and Sp3 negatively regulate and androgen does not directly regulate functional tumor suppressor 15-lipoxygenase 2 (15-LOX2) gene expression in normal human prostate epithelial cells

Abstract: In this project, we studied the gene regulation of 15-lipoxygenase 2 (15-LOX2), the most abundant arachidonate-metabolizing LOX in adult human prostate and a negative cell-cycle regulator in normal human prostate (NHP) epithelial cells. Through detailed in silico promoter examination and promoter deletion and activity analysis, we found that several Sp1 sites (i.e., three GC boxes and one CACCC box) in the proximal promoter region play a critical role in regulating 15-LOX2 expression in NHP cells. Several piec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 30 publications
4
36
0
Order By: Relevance
“…One possibility is Figure 6 Enforced expression of 15-LOX2 or 15-LOX2sv-b in early-passage NHP7 cells induces cell-cycle arrest and a senescence-like phenotype. NHP7 cells at P2 were plated at clonal density were either untransduced or infected with pBabe-EGFP, pBabe15LOX2-EGFP (two clones used, that is, FL-3 and FL-4; see Table 2), or pBabe15LOXsv-b-EGFP (two clones used, that is, SVb-1 and SVb-2; see Table 2 15-LOX2 and normal human prostate epithelial cell senescence B Bhatia et al through increased Sp1 transcriptional activity (Tang et al, 2004). In support, 15-LOX2 promoter constructs with the Sp1 sites mutated, when transfected into latepassage NHP6 cells, possess much lower promoter activities compared to the constructs with the intact Sp1 sites (Tang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One possibility is Figure 6 Enforced expression of 15-LOX2 or 15-LOX2sv-b in early-passage NHP7 cells induces cell-cycle arrest and a senescence-like phenotype. NHP7 cells at P2 were plated at clonal density were either untransduced or infected with pBabe-EGFP, pBabe15LOX2-EGFP (two clones used, that is, FL-3 and FL-4; see Table 2), or pBabe15LOXsv-b-EGFP (two clones used, that is, SVb-1 and SVb-2; see Table 2 15-LOX2 and normal human prostate epithelial cell senescence B Bhatia et al through increased Sp1 transcriptional activity (Tang et al, 2004). In support, 15-LOX2 promoter constructs with the Sp1 sites mutated, when transfected into latepassage NHP6 cells, possess much lower promoter activities compared to the constructs with the intact Sp1 sites (Tang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether 15-LOX2 induction resulted from transcriptional activation, we first measured the 15-LOX2 promoter activity in NHP6 cells transfected with the p15LOX2 (À726/ þ 80)-luc reporter construct (Tang et al, 2004). As shown in Figure 4B, increasing 15-LOX2 promoter activity was observed in NHP6 cells with increasing passages.…”
Section: Transcriptional Induction Of Both 15-lox2 and Its Splice Varmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently there were two other studies focused on the promoter regulation of 15-LOX-2 gene. Tang et al (9) reported that Sp1 positively and Sp3 negatively regulate and androgen does not regulate 15-LOX-2 gene expression in normal human prostate epithelial cells. Subbarayan et al (5) reported that 15-LOX-2 can be negatively regulated by its product 15-(S)-hydroxyeicosatetraenoic acid and PPARÁ through a PPAR half-site present in the 15-LOX-2 promoter region (-560 to -596).…”
Section: Introductionmentioning
confidence: 99%